Sifat-Sifat Matriks Ketetanggaan Pada Graf Petersen - Yuco Alsbaldo; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2021)
Graphs are used to represent discrete objects and the relationships between these objects. One of the best known and very popular examples of graphs is Petersen graph.Petersen graph is very popular because of its uniqueness as a counterexample in many places and has many interesting properties. Graphs can beexpressed in the form of a matrix adjacencywhich is denoted. When a graph can be expressed in the form of an adjacency matrix, its determinants and eigenvalues can be determined. This research is a theoretical research through literature study. The purpose of this study is to find out how the properties of the adjacency matrix on a Petersen graph are. The concept that will be discussed in this research is how the properties of the determinants and eigenvalues of the adjacency matrix on the Petersen graph. The result of the research is that the determinant of the adjacency matrix on the Petersen graph is positive with three different eigenvalues and can be diagonalized because the algebraic multiplicity is the same as the geometric multiplicity mA = mG